2021
DOI: 10.1108/ijaim-04-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

Does the impact of IFRS on audit fees differ between early and late adopters?

Abstract: Purpose This study aims to examine whether the impact of international financial reporting standards (IFRS) on audit fees differs between early and late adopters. Design/methodology/approach The authors use robust econometric estimation on a sample of 314 firms from both early and late IFRS adopting countries. Findings The authors find that IFRS is positively and significantly associated with an increase in audit fees for early adopters, but the impact is very weak for late adopters and insignificant in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
3
12
0
1
Order By: Relevance
“…Similarly, the variable AuditFee has mean values of 2.33 and 2.60 before and after IFRS convergence, respectively. These findings indicate that, on average, there is a substantial increase in the cost of equity and audit fees after IFRS convergence, which is consistent with the findings of previous research (Bansal, 2022;Tawiah, 2022). In terms of control variables, Table 2 reveals that, during the post-IFRS period, firms are generally larger in terms of size (Size), with higher stock beta (FirmBeta), return volatility (ReturnVolitility) and trading volume (Volume), more institutional ownership (InstOwn), increased sales (Sales) and a higher current ratio (CurrentRatio).…”
Section: Summary Statisticssupporting
confidence: 91%
“…Similarly, the variable AuditFee has mean values of 2.33 and 2.60 before and after IFRS convergence, respectively. These findings indicate that, on average, there is a substantial increase in the cost of equity and audit fees after IFRS convergence, which is consistent with the findings of previous research (Bansal, 2022;Tawiah, 2022). In terms of control variables, Table 2 reveals that, during the post-IFRS period, firms are generally larger in terms of size (Size), with higher stock beta (FirmBeta), return volatility (ReturnVolitility) and trading volume (Volume), more institutional ownership (InstOwn), increased sales (Sales) and a higher current ratio (CurrentRatio).…”
Section: Summary Statisticssupporting
confidence: 91%
“…Furthermore, they observed that Anglophone and common law African countries are more prone to adopting IFRS compared to Francophone countries. Tawiah (2022) assessed whether the effects of audit fees differ between early adopters and late adopters of IFRS. The study revealed a positive association between IFRS and increased audit fees among early adopters, while the impact on late adopters was found to be weak.…”
Section: Overview Of Ifrs Adoption and Compliance Literature In Africamentioning
confidence: 99%
“…The map shows citation trends as research continues in the domain. For instance, links existed between Tawiah (2022) and Agyei-Boapeah et al (2020), Boolaky et al (2020), Coffie and Bedi (2019) and Tawiah and Boolaky (2019) representing cited papers. Tawiah (2022) focused on whether the impact of IFRS on audit fees differs between early and late adopters.…”
Section: Jbsedmentioning
confidence: 99%
“…Ülkelerdeki yasal düzenlemeler ve yeni muhasebe uygulamaları, denetim ücretlerini etkilemektedir. Örneğin; UFRS'nin ilk uygulama yıllarında denetim ücretlerinde anlamlı bir artış tespit edilirken (Shan ve Troshani, 2016;Tawiah, 2021), bu etkinin ileriki yıllarda da sürdüğü gözlemlenmiştir (El Guindy ve Trabelsi, 2020).…”
Section: Düzenlemelerin Denetim üCretine Etkisiunclassified